Gamma-ray spectrum from thermal neutron capture on gadolinium-157. (22nd February 2019) - Hagiwara, Kaito; Yano, Takatomi; Tanaka, Tomoyuki; Reen, Mandeep Singh; Das, Pretam Kumar; Lorenz, Sebastian; Ou, Iwa; Sudo, Takashi; Yamada, Yoshiyuki; Mori, Takaaki; Kayano, Tsubasa; Dhir, Rohit; et al.
Abstract: We have measured the$γ$ -ray energy spectrum from the thermal neutron capture, ${}^{157}$ Gd$(n, γ)$, on an enriched$^{157}$ Gd target (Gd$_{2}$ O$_{3}$ ) in the energy range from 0.11 MeV up to about 8 MeV. The target was placed inside the germanium spectrometer of the ANNRI detector at J-PARC and exposed to a neutron beam from the Japan Spallation Neutron Source (JSNS). Radioactive sources ($^{60}$ Co, $^{137}$ Cs, and$^{152}$ Eu) and the$^{35}$ Cl($n$, $γ$ ) reaction were used to determine the spectrometer's detection efficiency for$γ$ rays at energies from 0.3 to 8.5 MeV. Using a Geant4-based Monte Carlo simulation of the detector and based on our data, we have developed a model to describe the$γ$ -ray spectrum from the thermal${}^{157}$ Gd($n$, $γ$ ) reaction. While we include the strength information of 15 prominent peaks above 5 MeV and associated peaks below 1.6 MeV from our data directly into the model, we rely on the theoretical inputs of nuclear level density and the photon strength function of${}^{158}$ Gd to describe the continuum$γ$ -ray spectrum from the${}^{157}$ Gd($n$, $γ$ ) reaction. Our model combines these two components. The results of the comparison between the observed$γ$ -ray spectra from the reaction and the model are reported in detail.